The Trajectory and Trend of International Political Economy in Southeast Asia - Miranda Paulina Tahalele; Ahmad Dhiaulhaq; Rhevy Adriade Putra; Roseno Aji Affandi; Lili Yulyadi Arnakim; Tirta Nugraha Mursitama (JAS (Journal of ASEAN Studies), 2022)
International political economy debates in Southeast Asia have expanded in the last decades from the perspectives of development theories in conjunction with the structure of states relations to the links between state-market-society. The article explores the studies of Southeast Asia’s political economy that has stimulated the debate over the past years and its future trends. It intends to analyse the trajectory of the issues and topics identified utilizing structured research of studies in scientific databases and derive discussion on its future topics by looking at the links between state-market-society. The existing topics related to issues of the political economy of Southeast Asia are grouped into themes related to development financing from traditional and emerging donors, State-Owned Enterprises, and regional integration. In addition, it captures the topics based on the trend that are proposed and emerged within the policy discussion and academic forums. The initiated issues are climate change and environment, the importance of sub-regional in ASEAN integration, and digitalisation and technological advancement.